An investigation of expertise in cycling: Eye tracking, Think Aloud and the influence of a competitor. (July 2020) - Massey, Hollie S.; Whitehead, Amy E.; Marchant, David; Polman, Remco C.; Williams, Emily L.
Abstract: Objectives: Two studies investigated expert-novice differences in information-seeking behaviour, cognitions and performance during cycling time trials (TT). Study 1 examined trained and novice cyclist's cognitions whilst performing a TT, using a Think Aloud (TA) protocol and eye-tracking techniques. Study 2 investigated expertise differences during alone and competitive TTs. Methods: in Study 1, six trained and seven novice cyclists performed a 16.1 km TT. In Study 2, eight trained and ten novice cyclists performed three 16.1 km TT; a baseline TT, an alone TT and a trial against a virtual competitor. In both studies, participants were asked to TA and in Study 1 they also wore mobile gaze-tracking glasses. Performance feedback and a simulated TT course were visually displayed during all trials, as was a virtual avatar during the competitor trial. Verbalisations were coded into primary and secondary themes. Cognitions and pacing strategies were compared between groups and across the duration of the TTs. In Study 1, eye-tracking data for total dwell time and gaze frequency were calculated for each area of interest (Time Elapsed, Power, Heart Rate, Cadence, Distance Covered, Speed and Course Scenery). Results: In Study 1, no significant differences were found in information-seeking behaviour between groups, however there were expertise differences in the cognitive strategies used. Trained cyclists' verbalisations were more performance-relevant (i.e., power output), whereas the untrained group were more focused on task completion (i.e., distance and time) and irrelevant information. Both groups talked more about distance and motivational thoughts in the later stages of the trial, and dwell time on distance feedback also increased in this final 4 km. In Study 2, the trained group performed faster than the untrained group but there were no significant differences in pace or performance between alone and competitive TTs for either group. Differences in cognitions were found between groups and across the TT duration. Conclusion: Both studies demonstrate that cognitive processes differ as a function of expertise during self-paced cycling time trials. There were no differences in information-seeking behaviour between trained and untrained cyclists and there was no effect of an opponent on pace or performance. Highlights: Trained cyclists verbalise more performance-relevant thoughts (i.e., power output). Untrained cyclists verbalise more thoughts related to task completion and irrelevant information. Both groups verbalised more distance and motivational thoughts during the final 4 km of the time trial. No between-group differences in information seeking behaviour were found. Pace was unaffected by the presence of a competitor in both groups.